Institutional Membership and Rural Development in Indonesia: Case Study of Three Villages in Purbalingga - Sutiyo, Sutiyo; Nurdin, Ismail (KOMUNITAS: International Journal of Indonesian Society and Culture, 2015)
This study aims to measure community membership in rural institution and analyze its benefits in rural development after Indonesian decentralization. To do so, a case study was conducted in Serang, Kedarpan and Sumilir village of Purbalingga District, Central Java Province. Respondents of this study consist of 232 people, and data are analyzed both qualitatively and quantitatively. Findings of this study present that diverse community groups exist, and most households become active members in one to two rural institutions. Neighbourhood, religious and farmer groups are the most active institutions in term of membership and carrying periodic meeting. Membership in rural institutions improves access to financial, physical and natural capital, but less in improving human capital. While most villagers are member of neighbourhood, farmer and religious groups, the village government does not build intensive interaction with these institutions in meetings to formulate village decision. Thus, the empowerment process is not optimally delivered, and the institutions cannot optimally help their members in addressing their livelihood problems. Some initiatives are performed by the institutions, but without government support, they result only limited benefits for the members. Thus, this study recommends the government to involve more institutions in village decision making, especially by improving the participation of neighbourhood, religious and farmer groups.